ENHANCING PROFESSIONAL NURSING COMPETENCE THROUGH ESP AND PORTFOLIO-BASED LEARNING: A QUANTITATIVE STUDY - Yoyok Febrijanto; Erva Elli Kristanti (Pedagogic Research-Applied Literacy Journal, 2026)
The integration of English for Specific Purposes (ESP) and portfolio-based learning has become increasingly important in nursing education to enhance students’ professional competence. This study aimed to examine the level of ESP competence and the implementation of portfolio-based nursing care, as well as to analyze the relationship and influence between these two variables among second-year nursing students at STIKES RS Baptis Kediri. A quantitative cross-sectional design was employed involving 153 second-year nursing students selected using total sampling. Data were collected using validated Likert-scale questionnaires measuring ESP competence and portfolio-based nursing care implementation. The data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results showed that students’ ESP competence and portfolio-based nursing care implementation were both at a good level. A strong and significant positive relationship was found between ESP competence and portfolio-based nursing care implementation (r = 0.684, p < 0.001). Regression analysis indicated that ESP competence significantly influenced portfolio-based nursing care implementation (B = 0.756, p < 0.001), explaining 46.8% of the variance. These findings suggest that integrating ESP into nursing education can significantly support portfolio-based learning and enhance professional nursing competence. The study recommends strengthening ESP instruction aligned with clinical documentation and reflective portfolio practices.